Strategic default in financial networks - Nizar Allouch; Maya Jalloul; Alfred Duncan (University of Kent, School of Economics, 2021)
This paper investigates a model of default in financial networks where the decision by one agent on whether or not to default impacts the incentives of other agents to escape default. Agents' payoffs are determined by the clearing mechanism introduced in the seminal contribution of Eisenberg and Noe (2001). We first show the existence of a Nash equilibrium of this default game. Furthermore, we develop an algorithm to find all Nash equilibria that relies on the financial network structure. The algorithm provides a ranking for the set of Nash equilibria, which can serve as a measure of systemic risk. Finally, we show that introducing a central clearing counterparty achieves the efficient equilibrium at no additional cost.
Keywords: C72; D53; D85; G21; G28; G33; 330; systemic risk; default; nancial networks; coordination games; central clearing counterparty; nancial regulation